Knowledge Technology Third Knowledge Technology Week, KTW 2011, Kajang, Malaysia, July 18-22, 2011. Revised Selected Papers - Lukose, Dickson; Ahmad, Abdul Rahim; Suliman, Azizah; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Third Knowledge Technology Week, KTW 2011, held in Kajang, Malaysia, in July 2011. The 29 revised full papers presented together with 9 short papers were carefully reviewed and selected from 105 submissions. KTW 2011 consisted of a number of co-located events. This volume contains selected papers from the proceedings of the Third Malaysian Joint Conference on Artificial Intelligence (MJCAI 2011), the Third Semantic Technology and Knowledge Engineering (STAKE 2011), and the International Workshop on Semantic Agents (IWSA 2012).
Third Malaysian Joint Conference on Artificial Intelligence (MJCAI 2011) -- Third Semantic Technology and Knowledge Engineering (STAKE 2011) -- International Workshop on Semantic Agents (IWSA 2012).
Keywords: Computer science; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Image Processing and Computer Vision; Information Systems Applications (incl. Internet).